2008
DOI: 10.1097/phm.0b013e31818377b6
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Injection of Elite Athletes with Career-Altering Chronic Groin Pain Who Fail Conservative Treatment

Abstract: Athletes returned to full elite-level performance in a timely and sustainable manner after regenerative injection therapy using dextrose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 18 publications
3
35
0
Order By: Relevance
“…20 Another study on sports-altering tendinosis (adductor and abdominal insertions) in elite rugby and soccer athletes resolved career-threatening chronic groin pain in Ͼ90% of athletes. 22 The speed and success rate for return to sport in the adductor/abdominal tendinosis study were the same as that reported with far more expensive surgical interventions. In this OSD study, similar efficacy was demonstrated, but it also represents the first study in an exclusively pediatric population, and the first study in which a tendon attachment on an apophysis was injected.…”
Section: Comparison With Relevant Findings From Other Published Studiessupporting
confidence: 65%
See 2 more Smart Citations
“…20 Another study on sports-altering tendinosis (adductor and abdominal insertions) in elite rugby and soccer athletes resolved career-threatening chronic groin pain in Ͼ90% of athletes. 22 The speed and success rate for return to sport in the adductor/abdominal tendinosis study were the same as that reported with far more expensive surgical interventions. In this OSD study, similar efficacy was demonstrated, but it also represents the first study in an exclusively pediatric population, and the first study in which a tendon attachment on an apophysis was injected.…”
Section: Comparison With Relevant Findings From Other Published Studiessupporting
confidence: 65%
“…Our plan for enrollment was to reach a minimum of 20 cases in each group, on the basis of a previous study using a similar injection treatment. 22 …”
Section: Ethics and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…There is substantial evidence from non-randomized prospective and retrospective studies as well as case reports that cannot be discussed here due to a limited size of this publication [17][18][19][20][21][22]65 ] . Similar results were demonstrated by Alfredson et al in peripheral tendinosis [52][53][54][55] and Topol et al in groin strains [79][80][81][82][83] .…”
Section: Clinical Effectivenesssupporting
confidence: 89%
“…The challenge will continue to determining which speci fi c growth factors should be used. The other viable possibility is injection of engineered, typespeci fi c tissue derived from stem-cell research [ 83,84,154 ] . Some variations of nanotechnology will be also added.…”
Section: Discussionmentioning
confidence: 99%